ҚИШЛОҚ ХЎЖАЛИГИ ЕРЛАРИНИ БАҲОЛАШ ВА УНИНГ НАТИЖАЛАРИДАН ФОЙДАЛАНИШНИНГ НАЗАРИЙ ВА УСЛУБИЙ АСОСЛАРИ - Сайдалиева Гўзал Абдурашидовна (MANAGEMENT AND ECONOMICS SCIENTIFIC RESEARCH JOURNAL, 2025)
This article addresses issues related to the use of earth’s resources, their natural and economic characteristics, regulatory legal acts, and so on.